The Impact of Shopee E-Commerce on Traditional Market Sales in Langkap Market, Bangkalan: A Sharia Economic Perspective - Syauqie Habibillah; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
This study aims to examine the impact of Shopee e-commerce on traditional market sales at Langkap Market, Burneh District, Bangkalan Regency, from a sharia economic perspective. The method used is descriptive qualitative through a literature review and interviews with the Head of Langkap Market as the main informant. The results show that the presence of Shopee e-commerce has caused a decline in sales, especially among clothing vendors in traditional markets, because consumers prefer the convenience and more competitive prices of digital platforms. This impact has forced vendors to switch to selling basic necessities that are still in demand in person. The COVID-19 pandemic has accelerated the shift in consumer behavior to e-commerce, although traditional markets continue to play a vital role in meeting urgent needs that cannot be met quickly by e-commerce. From a sharia economic perspective, this change requires a balance between technological advancements and the sustainability of micro-enterprises to maintain the principles of justice and welfare. This research provides important insights for developing strategies for preserving traditional markets in the digital era.